Answer :

12abx2 - (9a2 - 8b2)x - 6ab = 0

12abx2 - 9a2 x + 8b2x - 6ab = 0


3ax(4bx - 3a) + 2b(4bx - 3a) = 0 taking 3ax common from first two terms and 2b from last two


(4bx - 3a) (3ax + 2b) = 0


(4bx - 3a) = 0 or (3ax + 2b) = 0



Hence the roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses